2018
DOI: 10.1007/s12132-018-9346-3
|View full text |Cite|
|
Sign up to set email alerts
|

Understanding Living Conditions and Deprivation in Informal Settlements of Kisumu, Kenya

Abstract: Informal settlements are a common occurrence in developing countries. Each settlement, however, has unique living conditions which require improvement efforts that are specifically tailored to the settlement. This study, carried out in Kisumu's informal settlements, had two aims: to describe living conditions and to propose areas of improvement within the settlements. The study adopted two approaches: the living conditions framework and the multi-dimensional poverty index. Results indicate that deprivation is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 36 publications
(39 reference statements)
0
25
0
Order By: Relevance
“…Weak demand for safe emptying services in Kisumu was likely a combination of two factors: low income levels and the prevalence of unregulated, informal manual emptiers. Approximately half of our study population reported monthly household incomes lower than 10,000 KES (100 USD), which other studies estimated as the average income level in Kisumu LIAs [ 37 – 39 ]. Spread over time and amongst households sharing a toilet, safe emptying services represent a modest fraction of incomes (approximately 1%, considering annual costs of 5,000–9,500 KES per toilet shared by six households, S1 Table ); despite this, a one-off payment, especially if carried by a single household as is often the case, can represent over 50–100% of a household’s monthly income and therefore compete with other priority expenditures.…”
Section: Discussionmentioning
confidence: 91%
“…Weak demand for safe emptying services in Kisumu was likely a combination of two factors: low income levels and the prevalence of unregulated, informal manual emptiers. Approximately half of our study population reported monthly household incomes lower than 10,000 KES (100 USD), which other studies estimated as the average income level in Kisumu LIAs [ 37 – 39 ]. Spread over time and amongst households sharing a toilet, safe emptying services represent a modest fraction of incomes (approximately 1%, considering annual costs of 5,000–9,500 KES per toilet shared by six households, S1 Table ); despite this, a one-off payment, especially if carried by a single household as is often the case, can represent over 50–100% of a household’s monthly income and therefore compete with other priority expenditures.…”
Section: Discussionmentioning
confidence: 91%
“…Overall, these trends are consistent with other regions of the world, where since the onset of this pandemic, it has been clear that higher connectivity, particularly through air traffic, and higher population densities are key drivers in the introduction and growth of the epidemic. (35)(36)(37)(38)(39) The impact of population density is clearly illustrated by the projected new infections of COVID-19 in places like Djibouti and Rwanda. To compound this, close to 90% of urban settlements in Africa are comprised of informal settlements, most of which are overcrowded and lack basic amenities such as clean water and sanitation which are critical prevention measures for COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, these trends are consistent with other regions of the world, where since the onset of this pandemic, it has been clear that higher connectivity, particularly through air traffic, and higher population densities are key drivers in the introduction and growth of the epidemic. (35-39)…”
Section: Discussionmentioning
confidence: 99%
“…Over half of Kisumu's inhabitants live in dense, informal neighborhoods with limited public health infrastructure. 7,8 With assistance from 15 local community health volunteers (CHVs), we identified four to five households with children aged 3-9 months in each CHV's catchment area. Our purposive sampling strategy ensured that participants reflected the range of environmental conditions in the neighborhood.…”
mentioning
confidence: 99%